ESTADO DE LOS RECURSOS NATURALES DEL SALTO TEMBEY PRINCIPAL ATRACTIVO TURÍSTICO EN LA ZONA DE YATYTAY. ITAPÚA (Journal on studies and research of academic knowledge, 2017)
The present study of descriptive type and mixed approach was carried out in Salto del Tembey in the district of Yatytay, Itapúa. It describes the state of the natural resources adjacent to the main tourist attraction of Yatytay. The general objective has been to characterize the waterfall as a tourist resource in the district. The techniques and method of data collection have been the following: direct observation, photographic records, survey, satellite and cartographic images of the area. The Waterfall Tembey as a tourist resource has the following characteristics: it comprises a radius of approximately 1,500 meters. The biggest attraction of the area is the waterfall itself. The place has all the characteristics for a rational exploitation of tourism with some problems that could be solved with a good environmental management. It has infrastructure for tourism although in poor conditions. Regarding the state of natural resources, it was found that the soil is of basaltic origin, with landscapes of hills, the forest cover occupies almost the whole area of the water fall. The river banks do not have the minimum width of required as a wooded protection and in drought days the water presents a natural clear visual aspect, without apparent contamination or turbidity. The main anthropic activities come from the agricultural sector and the burning of solid waste which is the practice most used by the settlers. The most important problems perceived by the local residents constitute a pig farm, as well as the lack of sanitary landfill and the erosion. The population is favorable to collaborate in the maintenance of the resource and their perception of the place's environment care is of "careless". The data obtained through this environmental diagnosis could serve as references for a better environmental management of the place, considering that the resource is very frequented by tourists.
Keywords: Tourist resource; Tembey Falls; environmental problems